Social media in Primary Education: knowledge and use by participating teachers in a training environment - Bruno Moratón Cano; María Luna Chao; Sonia J. Romero Martínez (Tecnología, Ciencia y Educación, 2015)
In recent years, the use of social networks has grown to currently become important communication tools. In school education it is possible to take profits to the potential of social networks to work with students of different educational stages several curricular contents. At the same time, pupils can develop skills to use social networks properly. In the present study we assessed the degree of knowledge about social networks and the kind of use of a sample of Primary teachers. Furthermore, we compare teachers’ perception of utility and their disposition to use social networks after a training process. The majority of the participants consider social networks as useful or very useful. Nevertheless they have deeper knowledge of common social networks than of specific educational networks. Additionally, they seem to be unconscious of the characteristics and possibilities of the later. After training, the teachers increased their perception of utility and their disposition to incorporate social networks to their educational activities.